Pacemaker Remote Monitoring in the Pediatric Population: Is It A Real Solution?. Issue 5 (4th March 2015) - LEONI, LOIRA; PADALINO, MASSIMO; BIFFANTI, ROBERTA; FERRETTO, SONIA; VETTOR, GIULIA; CORRADO, DOMENICO; STELLIN, GIOVANNI; MILANESI, ORNELLA; ILICETO, SABINO
<x xml:space="preserve">Abstract</x> Background Clinical utility of remote monitoring of implantable cardiac devices has been previously demonstrated in several trials in the adult population. The aim of this study was to assess the clinical utility of remote monitoring in a pediatric population undergoing pacemakers implantation. Methods The study population included 73 consecutive pediatric patients who received an implantable pacemaker. The remote device check was programmed for every 3 months and all patients had a yearly out‐patient visit. Data on device‐related events, hospitalization, and other clinical information were collected during remote checks and out‐patient visits. Results During a mean follow‐up of 18 ± 10 months, 470 remote transmissions were collected and analyzed. Two deaths were reported. Eight transmissions (1.7%) triggered an urgent out‐patient visit. Twenty percent of transmissions reported evidence of significant clinical or technical events. All young patients and their families were very satisfied when using remote monitoring to replace out‐patient visits. Conclusions The ease in use, together with satisfaction and acceptance of remote monitoring in pediatric patients, brought very good results. The remote management of our pediatric population was safe and remote monitoring adequately replaced the periodic out‐patient device checks without compromising patient safety.